Characterization and estimation of dielectric constant of electrospun BaTiO3 nanofibers at different calcination temperatures using theoretical models. Issue 2 (February 2021) - Hedayati, Mehdi; Taheri-Nassaj, Ehsan; Yourdkhani, Amin; Borlaf, Mario; Rasekh, Shahed; Amirkhizi, Parisa; Sebastian, Tutu; Payandeh, Seyedhosein; Clemens, Frank Jörg
Abstract: The main aim of this work was to estimate the dielectric constant of electrospun BaTiO3 nanofibers (BT NFs ) using theoretical models. The effect of calcination temperatures on morphology and crystal structure of BT NFs was also investigated by using SEM, TEM, XRD and Raman spectroscopy. The dielectric constant of BT NFs was calculated by applying modified Maxwell Garnett and Yamada models on polymer nanocomposite films comprising stearic acid modified BT NFs in Polyvinylidene difluoride (PVDF) matrix. The results showed that although it was detected low tetragonality (1.0041) at lowest calcination temperature (850 °C), the better crystallization of BT and high tetragonality could be achieved at a calcination temperature of 1000 °C and above. Based on both theoretical models, the dielectric constant of BT NFs calcined at 850 °C (around 830) is lower than those calcined at 1000 °C (about 1300), which is the result of different tetragonality and grain size.